Physician Decision-Making And Trends In Use Of Cardiac Stress Testing To Diagnose Coronary Heart Disease In The United States, 1993–2010 - Ladapo, Joseph A. (Ann Intern Med, 2014)
BACKGROUND: Cardiac stress testing, particularly with imaging, has been the focus of debates about rising health care costs, inappropriate use, and patient safety in the context of radiation exposure. OBJECTIVE: To determine whether U.S. trends in cardiac stress test use may be attributable to population shifts in demographics, risk factors, and provider characteristics and evaluate whether racial/ethnic disparities exist in physician decision making. DESIGN: Analyses of repeated cross-sectional data. SETTING: National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey (1993 to 2010). PATIENTS: Adults without coronary heart disease. MEASUREMENTS: Cardiac stress test referrals and inappropriate use. RESULTS: Between 1993 to 1995 and 2008 to 2010, the annual number of U.S. ambulatory visits in which a cardiac stress test was ordered or performed increased from 28 per 10 000 visits to 45 per 10 000 visits. No trend was found toward more frequent testing after adjustment for patient characteristics, risk factors, and provider characteristics (P = 0.134). Cardiac stress tests with imaging comprised a growing portion of all tests, increasing from 59% in 1993 to 1995 to 87% in 2008 to 2010. At least 34.6% were probably inappropriate, with associated annual costs and harms of $501 million and 491 future cases of cancer. Authors found no evidence of a lower likelihood of black patients receiving a cardiac stress test (odds ratio, 0.91 [95% CI, 0.69 to 1.21]) than white patients, although some evidence of disparity in Hispanic patients was found (odds ratio, 0.75 [CI, 0.55 to 1.02]). LIMITATIONS: Cross-sectional design with limited clinical data. CONCLUSION: National growth in cardiac stress test use can largely be explained by population and provider characteristics, but use of imaging cannot. Physician decision making about cardiac stress test use does not seem to contribute to racial/ethnic disparities in cardiovascular disease.